Anxiety Disorders and Coronary Heart Disease - Ergashova Ma’mura Toshtemirovna; Khusainova Munira Alisherovna; Yarmatov Suvon Totlibayevich; Gafforov Xudoyor Xudoyberdiyevich (Peerian Journals Publishing, 2022)
According to the World Health Organization, mortality from cardiovascular diseases remains the highest in comparison with economically developed countries among both men and women. In recent years, the prevalence of the main risk factors for cardiovascular diseases in Uzbekistan has not changed significantly, at the same time, the level of emotional stress has increased significantly. The growth of psychosocial stress in the population is accompanied by an increase in the level of emotional tension, anxiety among the population. The prevalence of anxiety disorders in the population, according to various authors, ranges from 3 to 30%. Anxiety increases after mental trauma, acute and chronic somatic diseases and neuropsychiatric diseases. Thus, the severity of anxiety and the level of anxiety, reflecting the degree of personal distress, can be a kind of marker of chronic psychological stress. With an increase in the level of anxiety, there is a change in the activity of sympathoadreal, hypothalamic-pituitary–adrenal and renin–angiotensin–aldosterone systems -Moreover, it is naturally accompanied by changes in carbohydrate, protein, and lipid metabolism, procoagulant shifts in hemostasis, and impaired vascular endothelial function. All these disorders can lead to increased progression of atherosclerosis, increased coronary vascular tone, increased instability of atherosclerotic plaques, a tendency to thrombosis and contribute to the aggravation of the course of coronary heart disease (CHD). At the same time, the peculiarities of the influence of anxiety disorders on the course of coronary heart disease and quality of life have not been studied enough
Keywords: coronary heart disease; term; emotional stress